Applying Spatial Analysis Tools in Public Health: The Use of AERMOD in Modeling the Emission Dispersion of SO2 and NO2 to Identify Exposed Area to Health Risks - Jayadipraja, Erwin Azizi; Daud, Anwar; Assegaf, Alimuddin Hamzah; Maming, Maming (YCAB Publisher & IAKMI SULTRA, 2016)
Background: The cement industry is one of the main contributors of pollutant gasses in the environment through stack emissions.Aim: This study aims to model the dispersion of SO2 and NO2 gasses and to determine the area of the dispersion by American Meteorological Society – Environmental Protection Agency Regulation Model or AERMOD has been utilized by PT. Semen Tonasa (Tonasa Cement, Ltd.).Methods: Meteorological data from AERMENT was collected from reanalysis of MM5 data. While topographical data was extracted from SRTM30 satellite data. The model was carried out for a year, to cover both the dry and rainy season.Results: The result of the modeling showed that the peak value of the concentration of SO2 and NO2 pollutants for one hour are 135 Î¼g/m3 and 160 Î¼g/m3 respectively (quality standards of SO2 and NO2 are 900 Î¼g/Nm3 and 400 Î¼g/Nm3). The area of dispersion tends to be in the eastern area, such as District Minasatene (Sub-district Bontoa, Kalabbirang, Minasatene dan Biraeng), District Bungoro (Sub-district Biringere, Sapanang, Mangilu, Bulu Tellue) and District Labakkang (Sub-district Taraweang). Key words: Spatial analysis, AERMOD, AERMOD, cement factory, exposed area, SO2 and NO2